Synthesis, characterization, and spectroscopic properties of the new type of aminoquinoline-modified cyclotriphosphazenes - Palabiyik, Duygu; Balci, Ceylan Mutlu (Taylor & Francis Ltd, 2022)
The aminolysis reactions of hexachlorocyclotriphosphazene, [N3P3Cl6] (1a) and dispiro-2,2 '-biphenoxydichlorocyclotriphosphazene [N3P3Cl2[(2,2 '-biphenoxy)(2)] (1b) with 6-aminoquinoline (2) were carried out to examine the spectroscopic properties of cyclotriphosphazene derivatives combined with 6-aminoquinoline. For the first time, two new aminoquinoline-substituted cyclotriphosphazene derivatives (3a, b) were obtained in this study. Both compounds (3a, b) have been characterized by elemental analysis, FT-IR analysis, MALDI-TOF mass spectrometry, C-13, H-1, and P-31 NMR spectroscopies. The molecular structure of 3b has been confirmed by single crystal X-Ray crystallography. The crystal structure of 3b was investigated in detail to determine the remarkable intermolecular interactions. Furthermore, the photophysical properties of compounds 3a and 3b were determined by using UV/vis and fluorescence spectroscopies.
Keywords: Cyclophosphazene; amine; spectroscopy; quinoline; crystal structure